Affectivity in the Young Sartre's Intersubjective Theory - Puente, Carlos de la (2006)
The intersubjective theory that Sartre proposed in Being and Nothingness contends that human encounters are necessarily reifying. The author proposes that one of the constitutive theoretical elements of this pessimistic view of human encounters is Sartre’s conception of affectivity as a degradation of consciousness. The author explores this vision of affection that Sartre initially developed in his essay Outline of a Theory of Emotions, and concludes that it was this mode of understanding affectivity that later decisively influenced his contention in Being and Nothingness that the essence of human relations is conflict.